Late-time Optical and X-Ray Emission Evolution of the Oxygen-rich SN 1996cr - Daniel Patnaude; Kathryn E. Weil; Robert A. Fesen; Dan Milisavljevic; Ralph P. Kraft (The Astrophysical Journal)
When the ejecta of a supernova (SN) interact with the progenitor star's circumstellar environment, a strong shock is driven back into the ejecta, causing the material to become bright optically and in X-rays. Most notably, as the shock traverses the H-rich envelope, it begins to interact with metal-rich material. Thus, continued monitoring of bright and nearby SNe provides valuable clues about both the progenitor structure and its pre-SN evolution. Here we present late-time, multiepoch optical and Chandra X-ray spectra of the core-collapse SN, SN 1996cr. Magellan IMACS optical spectra taken in 2017 July and 2021 August show a very different spectrum from that seen in 2006 with broad, double-peaked optical emission lines of oxygen, argon, and sulfur with expansion velocities of ±4500 km s ^−1 . Redshifted emission components are considerably fainter compared to the blueshifted components, presumably due to internal extinction from dust in the SN ejecta. Broad ±2400 km s ^−1 H α is also seen, which we infer is shocked progenitor pre-SN, mass-loss, H-rich material. Chandra data indicate a slow but steady decline in the overall X-ray luminosity, suggesting that the forward shock has broken through any circumstellar shell or torus, which is inferred from prior deep Chandra ACIS-S/HETG observations. The X-ray properties are consistent with what is expected from a shock breaking out into a lower-density environment. Though originally identified as a Type IIn SN, based upon late-time optical emission-line spectra, we argue that the SN 1996cr progenitor was partially or highly stripped, suggesting a Type IIb/Ib SN.